2021
DOI: 10.3390/en14248387
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Fluorinated Polymers in the Water Management of Proton Exchange Membrane Fuel Cells: A Review

Abstract: As the hydrogen market is projected to grow in the next decades, the development of more efficient and better-performing polymer electrolyte membrane fuel cells (PEMFCs) is certainly needed. Water management is one of the main issues faced by these devices and is strictly related to the employment of fluorinated materials in the gas diffusion medium (GDM). Fluorine-based polymers are added as hydrophobic agents for gas diffusion layers (GDL) or in the ink composition of microporous layers (MPL), with the goal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 116 publications
0
7
0
Order By: Relevance
“…Especially, it will focus on the discussion of why fluorination is relevant and how it can be carried out to maintain both an adequate pore size distribution and a conductive state for electrochemical processes, as well as eventually the hetero-dopings (e.g., F, N, S, and P) in the catalysts that are necessary for the high ORR activity. So far, some review articles have addressed the fluorination effects on the properties and degradation of liquid ionomers and polymer membranes in fuel cells such as i) ionic conductivity, ii) chemical, mechanical, thermal, oxidative and hydrolytic stabilities, iii) the capability for fabrication into membrane electrode assemblies (MEAs), and iv) the role of fluorinated polymers in the water management, etc.. [17][18][19][20] However, the fluorination effects on the material properties and the fuel cell performance and stability of the catalysts and the catalyst layers have rarely been comprehensively discussed, which is exactly what this review paper strives to address. Additionally, the versatility of the gas/solid fluorination for such an aim will be highlighted.…”
Section: Introductionmentioning
confidence: 99%
“…Especially, it will focus on the discussion of why fluorination is relevant and how it can be carried out to maintain both an adequate pore size distribution and a conductive state for electrochemical processes, as well as eventually the hetero-dopings (e.g., F, N, S, and P) in the catalysts that are necessary for the high ORR activity. So far, some review articles have addressed the fluorination effects on the properties and degradation of liquid ionomers and polymer membranes in fuel cells such as i) ionic conductivity, ii) chemical, mechanical, thermal, oxidative and hydrolytic stabilities, iii) the capability for fabrication into membrane electrode assemblies (MEAs), and iv) the role of fluorinated polymers in the water management, etc.. [17][18][19][20] However, the fluorination effects on the material properties and the fuel cell performance and stability of the catalysts and the catalyst layers have rarely been comprehensively discussed, which is exactly what this review paper strives to address. Additionally, the versatility of the gas/solid fluorination for such an aim will be highlighted.…”
Section: Introductionmentioning
confidence: 99%
“…In general, the carbon paper is impregnated in polytetrafluoroethylene (PTFE) solution for hydrophobic treatment and then used as GDB to improve the drainage capacity, which in turn improves the performance of MEA at high current densities. 5 Although this method is simple to operate, it is difficult to achieve a uniform distribution of PTFE. Notably, PTFE is a fluorinated polymer with the (C 2 F 4 ) n structure, its molecular binding force is very weak, and the fluorine atoms exclude each other, so that the PTFE molecular chain structure is arranged in a spiral shape, which easily leads to the uneven distribution of PTFE on the carbon fiber.…”
Section: Introductionmentioning
confidence: 99%
“…The GDL is composed of gas diffusion backing (GDB) and a microporous layer (MPL). In general, the carbon paper is impregnated in polytetrafluoroethylene (PTFE) solution for hydrophobic treatment and then used as GDB to improve the drainage capacity, which in turn improves the performance of MEA at high current densities . Although this method is simple to operate, it is difficult to achieve a uniform distribution of PTFE.…”
Section: Introductionmentioning
confidence: 99%
“…25 Studies have shown that neat FEP and PFA performed higher friction coefficients when compared with PTFE due to their relatively irregular molecular chains. 28,29 Therefore, FEP and PFA have rarely been used to prepare self-lubricating components in place of PTFE but rather for other nonfriction fields such as insulating tubes or thin films, proton exchange membrane fuel cells, 30 and other electrochemical applications. 31 Moreover, few studies have been conducted so far on the tribological properties of composites filled with FEP and PFA as self-lubricant additives.…”
Section: Introductionmentioning
confidence: 99%